A Comparison of Retrobulbar Versus Topical Anesthesia in Trabeculectomy and Aqueous Shunt Surgery. Issue 1 (January 2018) - Theventhiran, Alex; Shabsigh, Muhammad; De Moraes, Carlos Gustavo; Cioffi, George A.; Kamel, Mohammed; Blumberg, Dana; Al-Aswad, Lama A.
Abstract : Purpose: The purpose of this study was to compare the required supplemental anesthesia and postoperative patient pain score in individuals undergoing glaucoma surgery under topical anesthesia (TA) versus retrobulbar anesthesia (RB). Materials and Methods: A retrospective, interventional, comparative cohort study of 261 eyes of 225 patients undergoing glaucoma and combined glaucoma with cataract surgery were included in the study. The main outcome measures were the amount of supplemental, systemic intraoperative anesthesia used and the postoperative pain scale between patients undergoing TA versus RB anesthesia. A secondary analysis was performed between combined glaucoma and cataract surgery versus glaucoma surgery alone. Results: About 6.2% patients complained of pain after glaucoma surgery (8.1% among TA group and 3.1% among RB group; P =0.049). Overall, pain tended to be mild with a mean score of 0.32 of 10 for TA and 0.08 of 10 for RB ( P =0.027). The amount of IV anesthetics used intraoperatively was lower in the RB anesthesia compared with the TA group (midazolam, P =0.042; fentanyl, P <0.001; propofol, P <0.001). In addition, patients undergoing RB anesthesia were less likely to use postoperative pain medication ( P <0.001). There was no difference in pain score ( P =0.707) or in the amount of IV anesthetics (all P >0.350) between eyes undergoing combined versus glaucoma surgery alone. Conclusions: Although supplemental anesthesia and pain scores were statistically increased in the topical group, the prevalence and the severity of pain was low. Therefore, TA is feasible and a reasonable option for glaucoma surgery. Furthermore, this conclusion applies when glaucoma surgery is performed alone or in combination with the other eye surgery.